Delineation of erythropoietic intermediates by flow cytometry - McGrath, Kathleen E. (Frontiers in Hematology, 2024)
Erythropoiesis occurs through specification from multipotent progenitors to erythroid restricted potential, expansion of erythroid progenitors, and terminal maturation of precursors to red blood cells. Acute anemia can induce changes at multiple stages of erythropoiesis, thus delineation and comparison of intermediates is critical to understanding this regulation. Historically, erythropoietic intermediates have been defined by functional colony forming assays (progenitors) or microscopy (precursors). While these sensitive single cell techniques have allowed detailed studies of the erythron, they do not allow for prospectively identifying and isolating live cells for experimental analyses. This has fueled development of flow cytometric criteria for analyzing the erythron from many different research groups for both the human and mouse systems. With these data, models of the immunophenotypic continuum of the erythron can be generated progressing from the earliest erythroid specific progenitors through late erythroblasts revealing remarkable conservation between human and murine cells. Recent data have also uncovered issues with previous classification schemes of erythromyeloid progenitors that are particularly problematic for erythroid progenitors. Applying these flow cytometric tools requires consideration of gating on a continuum in a reproducible fashion, fragments of macrophages caused by tissue dissociation on a proportion of erythropoietic cells, and ultimately application in anemia where signaling may impact the range of expression of specific immunophenotyping markers.